Lower body energy generation, absorption, and transfer in youth baseball pitchers - Pryhoda, Moira K.; Sabick, Michelle B. (Frontiers in Sports and Active Living, 2022)
An efficient baseball pitch will produce a high-velocity ball while minimizing risk of injury to the pitcher. This study quantified ground reaction forces and lower body power during the entire pitching motion of youth baseball pitchers to investigate how developing athletes generate and transfer energy from lower limbs to the throwing arm. These data provide a foundation for comparing youth pitching strategy and mechanics to optimal throwing mechanics and may aid in developing appropriate training suggestions for this age group. Full body three-dimensional (3D) motion capture and force platform data were collected on 23 youth pitchers performing fastballs thrown for strikes. Youth pitchers within this study used a ‘controlled drop’ strategy in which the COM was lowered during the stride phase followed by a weak forward drive motion. Ground reaction forces (GRFs) indicate that the drive leg propels the center of mass (COM) towards home plate while the stride leg braking force contributes to power generation up the kinetic chain. The stride hip generates energy assisting in energy flow up the kinetic chain as well as the creation of a stable base to rotate the trunk about. The lumbosacral joint generates the most energy of any joint studied, facilitating energy flow up the kinetic chain and underscoring the importance of core strength and coordination in proper pitching mechanics.